BRACHIAL ARTERY DIAMETER AS A PREDICTOR OF ENDOTHELIAL DYSFUNCTION IN SICKLE CELL DISEASE (Iraqi Journal of Medical Sciences, 2017)
Background: Sickle cell disease is hematological disease that affect the endothelial function. The hemoglobinopathy in this disease triggers erythrocyte polymerization and the sickling process leads to vascular occlusion, tissue hypoxia and subsequent reperfusion injury, thus inducing inflammation and endothelial injury.Objective: To assess the value of brachial artery diameter measurement as a predictor of the state of endothelium in sickled individuals.Methods: Thirty patients with sickle cell disease (15 females and 15 males) with a mean age of (27.0±8.9 yr) and 30 healthy controls (18 females and 12 males) with a mean age of (29.7±9.1 yr) participated in the study. Assessment of endothelial function done by studying physiological parameters, which included flow-mediated dilatation and endothelial-independent dilatation of the brachial artery depending on the measurement of the diameter of the blood vessel.Results: Endothelial independent dilatation was significantly lower in sickle cell disease patients (21.71±6.96) in comparison with that of the control group (26.81±6.31) despite the findings that both base line brachial artery diameter and intima media thickness were not significantly different between both groups.Conclusion: Brachial artery diameter assessment is a useful noninvasive predictor of endothelial dysfunction in patients with sickle cell disease. The reproducibility of the test in addition to its low cost and being free of biological hazards makes it optimum for assessing the state of the endothelium and may be used to monitor the response to treatment.Keywords: Sickle cell disease, flow-mediated dilatation, endothelial-independent dilatation, brachial artery diameter.DOI: 10.22578/IJMS.14.4.8
Keywords: Sickle cell disease; flowmediated dilatation; endothelialindependent dilatation; brachial artery diameter